Extraction of fermentable sugars and phenolic compounds from Colombian cashew (Anacardium occidentale) nut shells using subcritical water technology: Response surface methodology and chemical profiling - Luis J. Cruz-Reina; Jader Rodríguez-Cortina; Fabrice Vaillant; Israel Herrera-Orozco; Chiara Carazzone; Rocío Sierra (Chemical Engineering Journal Advances)
Subcritical water extraction (SCWE) is a novel technology that uses water at high pressure and temperature to recover bioactive compounds. While promising, further studies are needed to fully understand the potential of SCWE when applied to cashew nut shells (CNS), which are rich in phenolic compounds, carbohydrates, and other natural substances. This study aimed to evaluate SCWE applied to CNS from Vichada, Colombia, using a surface response methodology and to perform a comprehensive chemical profiling of the recovered extracts and the remaining solids. A Box-Behnken experimental design was employed to study the extraction process, focusing on variables such as temperature, pressure, and solid-to-solvent ratio. The liquid extracts were analyzed using ultra-high-performance liquid chromatography and gas chromatography coupled with mass spectrometry, while the extracted solids were characterized using Fourier-transform infrared spectroscopy and scanning electron microscopy. The liquid extracts revealed a variety of compounds, including xylose, glucose, arabinose, long-chain phenols, organic acids, and furans. Extraction conditions significantly influenced the distribution of these compounds, with the optimal conditions for extracting fermentable sugars and organic acids identified as 180 °C, 15 bar, and a 20:1 mL/g solid-to-solvent ratio. The resulting hydrochar comprised lignin (58.82 ± 3.44 %) and structural carbohydrates (approximately 40 %), showing thermal stability up to 200 °C, OH functional groups on its surface, and a textured morphology under microscopy. These by-products have potential applications in various fields. This study demonstrates that SCWE effectively recovers valuable compounds from CNS for use in fermentation processes, suggesting that the resulting hydrochar could be utilized in soil amendment, adsorption, or energy applications. SCWE is highlighted as an innovative and environmentally friendly technology for managing cashew residual biomass, promoting sustainability and circularity in this production chain.